Encyclopedia of Ophthalmology (Springer Berlin Heidelberg, 2018)
Rapid advances in pathogenetic insight, diagnostic and therapeutic modalities, and basic research continuously influence the state of the art in ophthalmology. This comprehensive encyclopedia offers a systematic and complete source of information including basic principles and novel updates, both clinical and scientific. The encyclopaedic format offers comprehensive access to focused information on all relevant topics in a clear and user-friendly manner. The spectrum ranges from short definitions, cross references, acronyms to disease chapters including epidemiology, symptoms and differential diagnosis, sections on diagnostic and therapeutic technologies, and comprehensive scientific summaries describing recent findings as well as results from relevant studies. The material is presented in a standardized, uniform and concise way throughout all clinical and academic sections. High-quality images highlight visual information and tables and graphs summarize important data. The encyclopaedia is available in book and electronic format which is linked to relevant ophthalmologic journals and is continuously updated. All chapters are authored by leading experts in the specific field. The target audiences are clinicians in ophthalmology and related specialties, researchers, and students.